PENGARUH DUKUNGAN SOSIAL DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI KELAS X SMA - Safitri, Fivin Amelia; Nurlaili, Eka Indah (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to analyze the influence of social support and learning motivation, both partially and simultaneously, on the economic learning outcomes of class X students at SMA Muhammadiyah 10 GKB Gresik. This research is a descriptive quantitative type that uses multiple linear regression analysis with the help of SPSS version 22 software. Data on social support and learning motivation were collected through questionnaires, while learning outcomes used second semester economic report card grades. The sample used was 120 class X students of SMA Muhammadiyah 10 GKB Gresik, with a simple random sampling technique using the Slovin formula. The results of this research show that (1) There is a positive and significant influence between social support on economic learning motivation with a significance value of 0.000 < 0.005, (2) There is a positive and significant influence between economic learning motivation on economic learning outcomes with a significance value of 0.000 < 0.005, (3) Simultaneously there is a significant positive influence between social support and learning motivation on economic learning outcomes with a significance value of 0.000 < 0.005. Keywords: Social Support, Learning Motivation, and Economic Learning Outcomes.